Numerical and experimental study of semi-rigid beam-to-column composite connections in cold-formed steel - Faisal, Amsyar; Tan, Cher Siang; Arizu, Sulaiman; Ma, Chau Khun (AIP Publishing, 2020)
The concept of cold-formed steel has been expanded recently from semi-rigid bolted moment connection to the composite construction. Partial strength beam-to-column composite connection is performed by anchoring reinforcement bars to the column member and embedded into the concrete slab. In this paper, series of numerical studies have been carried out to describe the complex interactions between different components in composite joint. Two laboratory test specimens of the non- and composite CFS joints have been tested and the results are used for validation of FE model. A 2 mm thick of hot-rolled steel gusset plate bolted by M12 grade 8.8 tension bolts are used to connect the I-shaped beam to the column. Multi-purpose software ABAQUS was used in this study to model a three dimensional (3-D) finite element model to investigate the non-linear behaviour of the composite connections. Approach of nonlinear material characteristics and geometric behaviour, contact and sliding between different elements and bolt pretension are proposed in this model. The proposed FE model can satisfactorily predict the moment-rotation relationship and load displacement correlation of the composite joints. The predictions agree very well with the experimental results and the proposed model can be used to represent the real behaviour of full-scale test.